The optimal dose of dexmedetomidine as a 0.59% ropivacaine adjuvant for epidural anesthesia in great saphenous varicose vein surgery, based on hemodynamics and anesthesia efficacy: a randomized, controlled, double-blind clinical trial - Zeng, Sisi; Li, Xuechao; Xu, Hongchun; Ye, Qin; Li, Zhaogang; Wang, Fangjun (Frontiers in Medicine, 2024)
Objective: To explore the optimal dose of dexmedetomidine as a 0.59% ropivacaine adjuvant for epidural anesthesia on perioperative hemodynamics and anesthesia efficacy in patients undergoing great saphenous varicose vein surgery.Methods: A total of 90 patients were randomly divided into three groups: 0.25 μg/kg dexmedetomidine combined with 0.59% ropivacaine epidural infusion group (ED1 group), 0.5 μg/kg dexmedetomidine combined with 0.59% ropivacaine epidural infusion group (ED2 group) and 0.75 μg/kg dexmedetomidine combined with 0.59% ropivacaine epidural infusion group (ED3 group). Hemodynamics, anesthesia efficiency and adverse reactions were recorded.